A urgência de coordenaç\~ao de políticas produtivas no território: Mirando o enfrentamento da crise institucional e econômica recente, de 2015 a 2022 - Aristides Monteiro Neto (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The article aims to discuss needs and opportunities for the accomplishment of the task of coordinating productive policies in the territory. It seeks to dialogue directly with national concerns for equitable territorial development and, thus, with the National Policy for Regional Development (PNDR). It evaluates the recent trajectory of the most relevant productive financing instruments with territorial impacts - namely, the rural credit policy, BNDES disbursements for productive activities, the amounts applied in the Constitutional Financing Funds (FCFs) of the regional policy and also evaluates the government's capacity to act through federal spending on public investment. As a result of the investigation, the work shows a high concentration of funding resources in more developed regions that are currently less accustomed to the sponsorship of the national redistributive pact for a just society
Keywords: H5; H77; R5; R51; R53; 330; public policies coordination; institutional crises; regional development; non-cooperative federalism; public finance